THE EFFECT OF APPLICATION OF SEARCH, SOLVE, CREATE, AND SHARE (SSCS) LEARNING MODEL ON STUDENTS' MATHEMATICS COMMUNICATION ABILITY BASED ON PREVIOUS KNOWLEDGE IN MATHEMATICS IN JUNIOR HIGH SCHOOL - Sahrul Hidayat; Hayatun Nufus; Ramon Muhandaz (Jurnal Prinsip Pendidikan Matematika, 2021)
This research aimed at investigating whether there was or not a difference on mathematical communication ability between students taught by using Search, Solve, Create, and Share (SSCS) learning model and those who were taught by using conventional learning; knowing whether there was or not a difference on mathematical communication ability among students having high, medium, and low prior knowledge in mathematics; and seeing whether there was or not an interaction between students’ prior knowledge in mathematics and SSCS learning model toward their mathematical communication ability. This study is a quasi-experimental study with a posttest-only control group design. The population in this study were all seventh grade students of SMP Negeri 3 Tambang for the 2019/2020 academic year. The sample in this study was class VII.1 as the experimental class and class VII.3 as the control class which was selected using simple random sampling. The data were collected using a test technique in the form of a test instrument for mathematical communication skills and PAM test questions. Analysis of the data used for hypotheses 1, 2 and 3 using a two-way ANOVA test. The results of data analysis show that there are differences in mathematical communication skills between students who follow the SSCS learning model and students who follow conventional learning, there are differences in mathematical communication skills between students who have high, medium and low PAM, and there is no interaction of PAM factors on mathematical communication skills. students at SMP Negeri 3 Tambang.